Groundwater in Urban Development : Assessing Management Needs & Formulating Policy Strategies - Foster, Stephen; Lawrence, Adrian; Morris, Brian (World Bank, Washington, DC, 2012)
People have clustered at the water's edge throughout civilization for the most fundamental of reasons: without water there is no life. Every major city in the world has a body of water or aquifer nearby, since rivers and lakes predetermined where people would gather and dwell, groundwater constitutes about 98 percent of the fresh water on our planet (excepting that captured in the polar ice caps). This makes it fundamentally important to human life and to all economic activity. Groundwater resources in and around the urban centers of the developing world are exceptionally important as a source of relatively low-cost and generally high-quality municipal and domestic water supply. At the same time, the subsurface has come to serve as the receptor for much urban and industrial wastewater and for solid waste disposal. There are increasingly widespread indications of degradation in the quality and quantity of groundwater, serious or incipient, caused by excessive exploitation and/or inadequate pollution control. The scale and degree of degradation varies significantly with the susceptibility of local aquifers to exploitation-related deterioration and their vulnerability to pollution. Management strategies need to recognize and to address the complex linkages that exist between groundwater supplies, urban land use, and effluent disposal. Groundwater tables have become the focus of keen interest in recent years, as the supplies of water underlying urban areas have dwindled and deteriorated, threatening the millions of people who live above. When conditions are right, aquifers refill regularly from infiltrating rainfall and runoff, although sometimes with a substantial time lag. But those favorable conditions are severely altered when the ground above is overbuilt.